Comparison of EAU and AUA guidelines in diagnosis and treatment of BPH [BPH tani ve teda vi̇si̇nde EAU ve AUA kila vuzlarinin karşilaştirilmasi] - (:unkn) unknown (My University, 2006)
Introduction: The treatment of benign prostatic hyperplasia (BPH), which is the most common cause of lower urinary tract symptoms (LUTS) of aging male, has been rapidly developing. New treatment options, especially, in the field of medical and minimal invasive treatment have been introduced in recent years. Overflowing the borders of "evidence-based medicine", intense advertisement efforts of some treatment modalities for BPH in mass media of our country let to a big confusion not only in the minds of the patients but also in men without LUTS. Therefore, the responsibility of the urologist in clarifying this confusion and donating the patients with true information has been increased. In this review, we analyzed in a comparative manner, the BPH guidelines of American Urology Association (AUA) and European Urology Association (EAU). Although, there are certain differences between two guidelines, basic ideology of approaching to BPH is similar. Both guidelines present very rich information regarding the diagnosis and management of BPH under the lights of "evidence-based medicine" and they are of utmost importance for every urologist who treats LUTS of aging men.
Keywords: AUA; Benign prostatic hyperplasia; EAU; Guideline